Restoring roots: possibilities of increasing biodiversity through community-engaged native planting in residential neighborhoods of Kansas City, Missouri - Herbel, Erich David (Kansas State University, 2024)
Many urban landscapes lack native plants that are integral to wildlife habitats and biodiversity (Müller et al., 2013; Reyes-Paecke, 2019). Biodiversity is linked to environmental benefits that impact public health, safety, and welfare. Studies show that well-connected patches and corridors of wildlife habitats are critical for biodiversity in urban landscapes, and greater biodiversity and resilience to climate change are achieved through an increase of native plants. While the need for improving biodiversity through native plants has been examined from a variety of landscape perspectives, including global, regional, rural, urban, public space, and private yards, little attention has been given to strategies that consider both public and private urban landscapes as a framework for improving wildlife habitat networks. To develop such strategies in urban landscapes, there must be acceptance and support from the residents. This study explores the possibilities for engaging residents in native plant activities to increase environmental benefits and wildlife habitats in residential neighborhoods. This is accomplished by examining the extent to which residents’ awareness of native plant benefits, interaction with native plants, and involvement in the community are associated with their preferences toward native plants in public and private landscapes. This study focuses on nine historically redlined, majority single-family, residential neighborhoods along the Brush Creek Corridor in Kansas City, Missouri, as a case to explore these issues. A spatial analysis was conducted to identify public and private areas with potential native plant and wildlife habitat connections. Survey data were then collected from residents (n=83) to assess the possibilities of engaging them in native plant activities through community involvement, public and private landscape scenarios, and landscape practices. The research findings were translated into spatial and social programming strategies and possible actions for planners and landscape architects to engage with communities through native plant activities to increase biodiversity. This study builds upon current literature by assessing variables that could impact residents’ preferences and their preferences toward native plants in both the public and private realms. The resulting strategies and actions could guide the collaboration of landscape architects and city planners with residential communities, initiatives, and programs in understanding ways to collectively engage urban residents in native plant activities to increase biodiversity, wildlife habitat, and environmental benefits in their neighborhoods.
Keywords: Community engagement; Urban residential landscape; Biodiversity; Native plants; Preference